2010
DOI: 10.3109/1354750x.2010.491557
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil to lymphocyte ratio predicts survival in advanced pancreatic cancer

Abstract: Elevated NLR is a predictor of shorter survival in patients with advanced PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
167
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(177 citation statements)
references
References 20 publications
6
167
0
Order By: Relevance
“…From then on, a large number of clinical studies have been performed to understand the neutrophil-cancer relationship. Clinical data have often related elevated circulating neutrophil counts or elevated neutrophil-to-lymphocyte ratios (NLRs) as a predictive parameter for poor outcome and formation of distant metastasis in patients with epithelial malignancies [367], including lung [368,170], gastric [159,163,369], renal cell carcinoma [370], ovarian [141], hepatic [143,148,371], pancreatic [138], colon cancer [145,372], and colorectal carcinoma [152] (Table 3). However, Caruso et al [200] observed that when analyzing the amount of tumor-infiltrated neutrophils in advanced gastric carcinoma, in female but not male, patients with higher TANs had a favorable prognosis.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
“…From then on, a large number of clinical studies have been performed to understand the neutrophil-cancer relationship. Clinical data have often related elevated circulating neutrophil counts or elevated neutrophil-to-lymphocyte ratios (NLRs) as a predictive parameter for poor outcome and formation of distant metastasis in patients with epithelial malignancies [367], including lung [368,170], gastric [159,163,369], renal cell carcinoma [370], ovarian [141], hepatic [143,148,371], pancreatic [138], colon cancer [145,372], and colorectal carcinoma [152] (Table 3). However, Caruso et al [200] observed that when analyzing the amount of tumor-infiltrated neutrophils in advanced gastric carcinoma, in female but not male, patients with higher TANs had a favorable prognosis.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
“…The pretreatment NLR was found to be an independent predictor of outcome in patients treated with systemic therapies for malignant mesothelioma [21], colorectal liver metastases [22], advanced pancreatic cancer [23], ovarian cancer [24], gastric cancer [25], and renal cell carcinoma [26].…”
Section: Introductionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) is an easily measured, reproducible, and inexpensive marker of systemic inflammation [21][22][23][24] that is associated with outcome in different cancer types. The pretreatment NLR was found to be an independent predictor of outcome in patients treated with systemic therapies for malignant mesothelioma [21], colorectal liver metastases [22], advanced pancreatic cancer [23], ovarian cancer [24], gastric cancer [25], and renal cell carcinoma [26].…”
Section: Introductionmentioning
confidence: 99%
“…The N/L ratio was calculated from the differential count by dividing the absolute neutrophil count by the absolute lymphocyte count. An N/L ratio ≥5 was considered elevated in accordance with the literature 8, 11, 17, 18…”
Section: Methodsmentioning
confidence: 81%
“…The tumor cells then produce chemokines, cytokines, and prostaglandins, which recruit inflammatory cells, which then subsequently trigger cancer‐related inflammation and further facilitate various tumor‐promoting effects 7. The neutrophil : lymphocyte (N/L) ratio has been shown to reflect the immune response and has been identified as a prognostic marker in many cancers, including gastrointestinal tract malignancy, non‐small cell lung cancer, cervical cancer, hepatocellular carcinoma, pancreatic cancer, ovarian cancer, and soft‐tissue sarcoma, reflecting a consistently decreased survival in patients with a high N/L ratio 8, 9, 10, 11, 12, 13, 14, 15. In addition, N/L ratio is reportedly correlated to incidental microcarcinoma in thyroid goiters, further indicating its potential as a diagnostic marker 16.…”
Section: Introductionmentioning
confidence: 99%